Aux frontières poreuses des cartes palestiniennes et de l'art contemporain - Anaïs Farine (Revue des Mondes Musulmans et de la Méditerranée)
Numerous contemporary Palestinian artists take on maps, either as patterns (classical maps simply emerge in the space of their work) or as conceptual models to structure their projects. Through the study of videos such as M* of Bethlehem [Ayreen Anastas, 2003], Red, Dead and Mediterranean [Akram Al-Ashqar, 2006], and We Began by Measuring Distance [Basma Al-sharif, 2009], we attempted to examine the displacement of artistic boundaries and the representation of geopolitical space within contemporary Palestinian moving images. Through investigating the different devices put in place by the three artists in order to reclaim the territory and give it meaning and unity, our study reveals that these works address with great subtlety the space concerns of a particular movement in contemporary art and have therefore become essential.